Empowering Evaluation PKM: A Mentoring Program for Young Elementary School Teachers in Designing Authentic Assessments Based on Local Potential - Salim Marpaung , Agus; Su'aidah Pulungan , Putri (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
The young teacher mentoring program at Pematang Nibung Public Elementary School 23, located in Pematang Nibung Village, Medang Deras District, Batu Bara Regency, North Sumatra, aims to improve teachers' skills in designing authentic assessments based on local potential. The program's background focuses on the challenges faced by teachers in remote areas, including a lack of resources and training in designing effective assessments. Authentic assessment is expected to increase student motivation and learning relevance, so that learning outcomes become more optimal. The research methods used in this program include needs analysis, intensive training, assessment simulations, mentoring by mentors, and evaluation and follow-up. The subjects of this community service were six teachers at Pematang Nibung 23 Public Elementary School, with the data collection instrument being an observation sheet to observe the participants' activities during the activity. The data obtained is processed and presented in descriptive form with a quantitative approach. The results of this program are expected to be seen in improved teacher assessment quality, which in turn will improve student learning outcomes. More relevant and contextual assessments are expected to help students better understand the subject matter. Furthermore, this program aims to increase teacher confidence in implementing innovative assessments based on local potential. Through ongoing evaluation, this program is expected to have a significant positive impact on education in Pematang Nibung Village and serve as a model for other areas facing similar challenges.